Metrics for Performance Improvement in Organisations Using Scrum, ITIL and CMMI - Bayona-Oré, Sussy (2022)
It is very important to understand the metrics that are applied within IT processes in today's industry, why they are important, and in what types of companies they are used. This article presents the results of a systematic literature review of some of the most widely used metrics exposed in the literature, referring to Scrum, ITIL and CMMi practices. The objective is to determine the scientific progress in this field and to identify the candidate metrics that can be used later in a metrics integration model, designed to help monitor IT services to improving the performance of organisations that use Scrum, CMMi and ITIL. The exploratory search found 1,196 articles, of which 198 were reviewed, from which 31 were finally chosen. From these, a total of 297 metrics were identified, of which 112 (38%) are for Scrum, 98 metrics (33%) are for ITIL, and 87 (29%) are for CMMi. Most of these metrics are used in European companies.